Sliding Mode Position Observer of PMSG Considering Salient-pole Effect - XIAO Lei; XU Junfeng; ZHANG Zhaoyang; WEN Yuliang; HE Yaping (Kongzhi Yu Xinxi Jishu)
It analyzed the mathematical model of the interior permanent-magnet synchronous motors (IPMSM) using for the directdriven permanent magnet synchronous generator (D-PMSG). Through the mathematical deformation, it proposed a new sensorless method based on sliding mode observer for a IPMSM. The model is all about the q-axis inductance, not the d-axis inductance. Dual filters are set in series to extract the electromotive force information, and then filter phase shift is measured for angle compensation in real-time at different speeds. Simulation and experimental results prove the validity of the control strategies.